Transmigrated mandibular canines: clinical considerations and orthodontic biomechanics for the approach of orthodontic traction. A scoping review (Research, Society and Development, 2021)
This scoping review aims to identify the clinical considerations and orthodontics biomechanics of applying the orthodontic traction approach to transmigrated mandibular canines. The search strategy followed the PRISMA for scoping reviews and was based on six databases, Cochrane C.R.C. Trials, BVS, PubMed (NLM), Google Scholar, Web of Science, and SCOPUS, and included articles published as recently as February 2021. The records had to identify lower canines traction protocols and outcomes. The publications obtained had to meet criteria for the structure of the research and bibliography. The search included combinations of the keywords lower canine, cuspid, and transmigration, along with the terms biomechanics and scoping review in the databases. Only after a consensus of the three reviewers had been reached were the articles retrieved. When a transmigrated lower canine has already erupted, orthodontics biomechanics traction begins by bonding tooth buttons and/or bracket prescriptions: MBT 0.022” x 0.028”, Roth 0.018” x 0.022”, and/or Beggs rectangular arches, ligatures, and elastics. Surgical interventions may be added. The treatment time varied from 22 months to 3.6 years. The final occlusal relationships were satisfactory and did not cause damage to the surrounding tissues. Among the selected articles, the orthodontic biomechanics showed the complexity of the movements. An appropriate occlusion and stability were achieved. Failures in the approach were also found. The clinical considerations show this approach to be viable but to have inherent risks, which include the proximity of the canines to the lower incisor roots.